A Review: Modern Coral Characterization Studies in Malaysia - Misman, Nurul Nadiah; Zakariah, Muhammad Noor Amin; Wan Saelan, Wan Nurzalia; Shaari, Hasrizal; Mohd Noh, Khairul Arifin (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2023)
Coral reefs are highly diverse and productive ecosystem in the ocean that provides various goods services to human and environment. Located within the renowned ‘Coral Triangle’ region, Malaysia is one the thriving countries in Southeast Asia that possess rich marine resources and coral reefs. Like other coral reef around the world, coral reefs in Malaysia are exposed to multiple threat that jeopardize their well-being. Those relying on these ecosystems may face severe consequences if they are lost. In recent decades, research on characterizing modern coral reefs has increased in Malaysia, including identifying key species and their distribution, understanding the factors that control coral growth and assessing the impacts of environmental stressors on reef health. This study is aimed to provide an overview of the current state of knowledge of modern coral characterization studies conducted in Malaysia. It presents the distribution maps of these coral reef studies conducted throughout Malaysia and discusses the techniques employed to characterize them. Most of the studies was conducted in South China Sea, particularly in East Coast of Peninsular Malaysia with Tioman Island, Pahang being identified as having the greatest number of studies. And, visual assessment have the higher frequency of use in characterizing Malaysia coral reef. Going forward, future studies in Malaysia should continue to explore others Malaysia reef, and techniques for characterizing coral reefs, while also conduct more studies in locations with limited research. These studies could have served as foundation resource for future conservation efforts in the face of ongoing threat and challenges.